The Cambridge companion to natural law jurisprudence - Duke, George, 1974-; George, Robert P. (Cambridge, United Kingdom ; New York, NY, USA : Cambridge University Press, 2017)
This collection provides an intellectually rigorous and accessible overview of key topics in contemporary natural law jurisprudence, an influential yet frequently misunderstood branch of legal philosophy. It fills a gap in the existing literature by bringing together leading international experts on natural law theory to provide perspectives on some of the most pressing issues pertaining to the nature and moral foundations of law. Themes covered include the history of the natural law tradition, the natural law account of practical reason, normativity and ethics, natural law approaches to legal obligation and authority and constitutional law. Creating a dialogue between leading figures in natural law thought, the Companion is an ideal introduction to the main commitments of natural law jurisprudence, whilst also offering a concise summary of developments in current scholarship for more advanced readers
Introduction / George Duke and Robert P. George -- Aquinas and natural law jurisprudence / John Finnis -- Natural law, God and human dignity / Robert P. George -- Early modern natural law theories / Knud Haakonssen -- Metaphysical foundations of natural law theories / Jonathan Crowe -- Natural law, basic goods, and practical reason / Christopher Tollefsen -- Practical reason in the context of law / Veronica Rodriguez-Blanco -- Hume, virtue and natural law / Thomas Pink -- Natural law reasoning in applied ethics / Jacqueline Laing -- Law as an idea we live by / N.E. Simmonds -- The moral impact theory, the dependence view, and natural law / Mark Greenberg -- The ideal dimension of law / Robert Alexy -- Two unhappy dilemmas for natural law jurisprudence / Mark C. Murphy -- The common good / George Duke -- Natural law theory and constitutionalism / Gerard V. Bradley -- Opening the doors of inquiry: Lon Fuller and the natural law tradition / Kristen Rundle
Includes bibliographical references and index
Keywords: Natural law